Safe public debt: Towards and operational definition - Xavier Debrun (Romanian Journal of Fiscal Policy (RJFP), 2015)
The paper proposes an operational definition of safe public debt levels and discusses various concrete approaches to calculate them. A public debt level is considered safe if it is associated with a low probability of reaching levels likely to generate significant economic costs within a given time frame. Like debt sustainability assessments, implementing such a broad definition requires medium-term projections of the debt-to-GDP ratio. This implies that different sets of plausible assumptions can yield fairly different "safe2 debt levels for the same country. However, the proposed framework has the merit to force policymakers and analysts to be explicit about the assumptions underlying their calculations.
Keywords: E62; H62; H63; 330; public debt; primary surplus; uncertainty